Analisis Parade Budaya Colorful Medan Night Carnival dalam Memperkuat City Branding Kota Medan sebagai Destinasi Wisata Multikultural - Eni Kusuma Amalia Ningrum; Vivianti Novita (Yayasan Literasi Sains Indonesia, 2026)
This study aims to examine the contribution of the Colorful Medan Night Carnival Cultural Parade in strengthening Medan City’s city branding as a destination based on cultural diversity. The development of urban tourism demonstrates that cultural identity plays a strategic role in enhancing destination competitiveness through city image formation, the creation of meaningful tourism experiences, and the strengthening of local community participation. This study employed a qualitative method with a descriptive approach. Data were collected through field observations, in-depth interviews, documentation, and relevant literature reviews. The data analysis process was conducted through several stages, including data selection and organization, data presentation, and interpretation to formulate research conclusions.The findings indicate that the Colorful Medan Night Carnival serves as a cultural representation space that showcases the ethnic diversity, traditional values, and creativity of Medan’s communities. The cultural parade functions not only as a form of entertainment or tourism attraction but also as a strategic communication instrument for constructing city identity through cultural symbols, visual aesthetics, performing arts, and authentic tourism experiences. The involvement of various stakeholders, including local government, cultural communities, local residents, and tourists, plays an essential role in supporting the sustainability of the event as part of the city branding strategy. This study concludes that the Colorful Medan Night Carnival contributes to strengthening Medan’s image as a multicultural city while enhancing its position as a culture-based tourism destination.